EFEKTIVITAS MODEL PEMBELAJARAN CONTEXTUAL TEACHING LEARNING TERHADAP HASIL BELAJAR ANATOMI PERNAPASAN SISWA KELAS 5 SEKOLAH DASAR - Alif Fia Amin Utaminingsih; Ika Safitri Purwandari; Fatika Meilani Cahya Arifaputri; Wahyu Kurniawati; Anisya Al Husna (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2024)
Â Understanding of respiratory anatomy is important for students to maintain health and quality of life. Gulurejo Village, with limited access to information and technology, presents challenges in implementing innovative learning models. The Contextual Teaching and Learning (CTL) learning model offers a potential solution in improving learning outcomes. This study aims to evaluate the effectiveness of the CTL model on the learning outcomes of respiratory anatomy of grade 5 students in Gulurejo Village by applying a descriptive qualitative approach through observation, interview, and data analysis. Data was collected from grade 5 elementary school students in Gulurejo Village. The results showed that the CTL model was effective in improving the learning outcomes of respiratory anatomy of grade 5 students in Gulurejo Village. CTL helps students understand abstract concepts by relating them to real-life context experiences. This is evidenced by a positive and pleasant learning experience for students, positive student perceptions of CTL effectiveness, and a significant increase in student learning outcomes in all aspects of assessment